". . . I've Gone Through This My Own Self, So I Practice What I Preach . . . ": Strategies to Enhance Understanding and Other Valued Outcomes in HIV Vaccine Trials in South Africa. (October 2016) - Slack, Catherine; Thabethe, Siya; Lindegger, Graham; Matandika, Limba; Newman, Peter A.; Kerr, Philippa; Wassenaar, Doug; Roux, Surita; Bekker, Linda-Gail
There has not been enough study of the processes by which site staff help participating community members and potential participants to understand complicated concepts for HIV vaccine trials. This article describes strategies reported in six focus group discussions with Community Advisory Board members, educators, and consent counselors at an active HIV vaccine trial site in South Africa. Thematic analysis identified a considerable range of strategies, and findings suggest that such staff do not only try to promote understanding of critical information but also try to build trust in communicated information, to respect cultural differences, and to promote voluntariness. Findings also suggest occasional tensions between these implicit goals. Actual engagement and consent encounters at HIV vaccine trial sites should be observed, recorded, and analyzed; and the relationship between practices and valued outcomes should be assessed. These efforts may help to make consent-related encounters as "potent" as possible given finite resources.